A systematic review and meta-analysis of reablement interventions for people in permanent residential aged care homes. (10th October 2022) - Rahja, Miia; Laver, Kate; Whitehead, Craig; Pietsch, Ann; Oliver, Eliza; Crotty, Maria
Abstract: Background: Most evidence for reablement comes from community-based interventions. Objective: To determine the effect of reablement interventions provided in permanent residential aged care (PRAC) homes on residents' level of function in activities of daily living (ADL) and quality of life (QoL). Design: Systematic review and meta-analysis. Setting: PRAC homes. Subjects: Residents in PRAC. Methods: Six databases and grey literature were searched until November 2021. Quantitative studies involving a control group or pre-post evaluation were included. Outcomes of interest were the effectiveness of the reablement intervention on overall ADL or QoL in the last available follow-up. Results: Twelve studies involving 2, 620 residents were included. The reablement interventions varied; the primary focus areas were organisational approaches (e.g. educating staff; n  = 10) and improving physical function (e.g. increasing physical activity; n  = 9). Not all studies could be pooled in the meta-analysis due to reported data and heterogeneity. There was no significant effect of reablement intervention versus usual care on ADL function (five studies, standardised mean difference (SMD): 0.17, 95% confidence interval (CI): −0.25 to 0.59, very low quality evidence). Reablement appeared more beneficial than usual care in improving QoL; however, the overall effect was not statistically significant (four studies, SMD: 0.73, 95% CI: −0.07 to 1.52; very low quality evidence). Conclusions: Few studies focus on reablement in PRAC homes and their clinical heterogeneity is considerable. There is insufficient evidence for reablement in terms of improving ADL or QoL for residents in PRAC. Tools that are more sensitive to change may be beneficial.